Pathogenicity and protective effect of rough mutants of Salmonella species in germ-free piglets - Dlabac, V; Trebichavský, I; Reháková, Z; Hofmanová, B; Splíchal, I; Cukrowska, B (Infection and immunity, 1997)
In this study, two stable, rough, streptomycin-sensitive Salmonella mutants with different types of genetic defects were used to colonize groups of germ-free (GF) piglets. The lipopolysaccharide (LPS) of Salmonella typhimurium SF 1591 was of the Ra chemotype (complete core), whereas the LPS of the S. minnesota mR 595 deep-rough mutant contained only lipid A and 2-keto-3-deoxyoctulosonic acid (Re chemotype). Both strains readily colonized the intestinal tracts of GF piglets and were stable during the whole experiment. All animals survived, and only transient fever was observed in some piglets colonized with the SF 1591 strain. Finally, streptomycin and virulent, smooth, streptomycin-resistant S. typhimurium LT2 were administered perorally 1 week later. All piglets colonized previously with the deep-rough mutant mR 595 died of sepsis, in contrast to piglets infected with the LT2 strain and colonized with the SF 1591 mutant, all of which survived. This difference is explained by the penetration of the mesenteric lymph nodes, spleen, and liver by great numbers of live bacteria in the latter case, resulting in prominent systemic and local immune responses. On the other hand, live bacteria were found only rarely in the mesenteric lymph nodes of animals colonized with the mR 595 strain and a negligible antibody response was observed.
Keywords: mutace; Virulence; Animals; Salmonella Infections, Animal; gnotobiologické modely; Swine, Miniature; virulence; Germ-Free Life; zvířata; Salmonella; miniaturní prasata; salmonelová infekce u zvířat; prasata; Swine; Mutation